Effect of Cyclosporine on Lesion Growth and Infarct Size within the White and Gray Matter - Ong, Elodie; Mewton, Nathan; Bouvier, Julien; Chauveau, Fabien; Ritzenthaler, Thomas; Mechtouff, Laura; Derex, Laurent; Buisson, Marielle; Berthezène, Yves; Ovize, Michel; Nighoghossian, Norbert; Cho, Tae-Hee (Frontiers in Neurology, 2017)
Background In a recent trial, cyclosporine A (CsA) failed to reduce infarct size in acute stroke patients treated with intravenous thrombolysis. White matter (WM) and gray matter (GM) may have distinct vulnerability to ischemia and response to therapy. Using final infarct size and lesion growth as endpoints, our objectives were to (1) investigate any tissue-specific effect of CsA and (2) compare WM and GM response to thrombolysis. Materials and methods We analyzed 84 patients from the randomized and placebo-controlled CsA-Stroke trial, who underwent MRI both on admission and at 1 month. Lesion growth was defined voxel-wise as infarcted tissue at 1 month with no visible lesion on baseline diffusion-weighted imaging. After automatic segmentation of GM/WM, final infarct size and lesion growth were compared within the GM and WM. Results Occlusion level was distal (>M1) in 51% of cases. No significant difference in GM/WM proportions was observed within final infarcts between treatment groups (P = 0.21). Infarct size within the GM or WM was similar between the CsA and control groups [GM: 9.2 (2.4; 22.8) with CsA vs 8.9 (3.7; 28.4) mL with placebo, P = 0.74; WM: 9.9 (4.7; 25.4) with CsA vs 14.1 (5.6; 34.1) mL with placebo, P = 0.26]. There was no significant effect of CsA on lesion growth in either the GM or WM. Pooling all patients, a trend for increased relative lesion growth in WM compared to GM was observed [49.0% (14.7; 185.7) vs 43.1% (15.4; 117.1), respectively; P = 0.12]. Conclusion No differential effect of CsA was observed between WM and GM. Pooling all patients, a trend toward greater lesion growth in WM was observed.